Telematics and computing : 8th International Congress, WITCOM 2019, Merida, Mexico, November 4-8, 2019 : proceedings /: 8th International Congress, WITCOM 2019, Merida, Mexico, November 4-8, 2019 : proceedings. ([2019]) - Unknown
No abstract available